Coyote lost and found - Gemeinhart, Dan (Henry Holt Books for Young Readers, 2024)
Almost a year after settling down in Oregon, Coyote embarks on a cross-country road trip with her dad to scatter her mom's ashes, but the journey takes an unexpected turn when she realizes the secret to the chosen resting place lies in a lost book.